Examining the teaching, assessment and research activities of the South African economics departments - Yu, D.; Jacobs, A. (South African Journal of Higher Education, 2026)
This study examined the staff profile, as well as teaching, assessment and research activities of 17 Economics Departments in recent years by consulting information from various sources. The results showed there has been an improvement in the staff qualifications such as a higher proportion of staff with a Doctorate degree and a higher number of departments with at least one staff getting the National Research Foundation rating. As far as the courses offered are concerned, at undergraduate level, along with Microeconomics and Macroeconomics, other commonly offered modules included Econometrics, Mathematical Economics, Development Economics, Labour Economics, Public Economics and International Economics. At Honours level, only five departments offered the Research Methods module, whereas Development Economics, Mathematical Economics, Public Economics, Monetary Economics and Labour Economics were offered by many departments. Furthermore, the results of the primary survey questionnaire on first-year Economics teaching and assessment practices showed that pre-recorded videos were used to complement face-to-face contact, while many departments had tutorials as one of the continuous assessment tasks. Lastly, upon examining five departments with 5-year (2016-2020) accredited journal article publications information available, it was found that collaboration amongst staff and/or with students represented the biggest proportion of these publications.